Exercise improves behavioral dysfunction and inhibits the spontaneous excitatory postsynaptic current of D2-medium spiny neurons - Zhao, Gang; Zhang, Danyu; Qiao, Decai; Liu, Xiaoli (Frontiers in Aging Neuroscience, 2022)
The abnormal function of striatal medium spiny neurons (MSNs) leads to the excitation-inhibition imbalance of the basal ganglia, which is an important pathogenic factor of Parkinson's disease (PD). Exercise improves the dysfunction of basal ganglia through neuroprotective and neuroreparative effects, which may be related to the functional changes of expresses D2 receptors MSNs (D2-MSNs). In this study, D2-Cre mice were selected as the research objects, the PD model was induced by unilateral injection of 6-OHDA in the striatum, and the 4-week treadmill training method was used for exercise intervention. Using optogenetics and behavioral tests, we determined that the average total movement distance of PD and PD+Ex groups was significantly lower than that of the Control group, while that of the PD+Ex and PD+Laser groups was significantly higher than that of the PD group, and the two intervention methods of exercise and optogenetic-stimulation of the D2-MSNs had basically similar effects on improving the autonomic behavior of PD mice. To further investigate the cellular mechanisms, whole-cell patch clamp recordings were carried out on D2-MSNs. We found that exercise decreased the frequency and amplitude of spontaneous excitatory postsynaptic current (sEPSC) and increased the paired-pulse radio of D2-MSNs while leaving basic electrophysiological properties of MSNs unaffected. Combined with behavioral improvement and enhanced D2R protein expression, our findings suggest the inhibited sEPSC of D2-MSNs may contribute to the behavioral improvement after exercise.